PENINGKATAN PERTUMBUHAN IKAN SIDAT (ANGUILLA BICOLOR) DENGAN PEMANFAATAN PEDICLE KERANG LENTERA SEBAGAI BAHAN PAKAN - Jandri Fan Ht. Saragi; Ria Retno (LPSDI Bina Patria, 2022)
The market demand for eel is very high. In January – August 2011 the export volume of eel decreased by 39.1% from the same period in 2010. The decline in exports was the impact of constraints on eel cultivation, namely the long growth of fish. A good feed for eels is fresh meat feed from fish, crustaceans, and shellfish. The composition of the feed has an impact on the high cost of feed production. Brachiopoda lingulata are often found in the waters of Batubara Regency as